Comparison of braking performance between mechanical and dynamic braking for Electric Powered Wheelchair - Muhamad Asyraf, Shahrom; Mohamad Heerwan, Peeie; Mohamad Izhar, Ishak; Muhammad Zulhilmi, Ismail; Muhammad Solehuddin, Ibrahim (IOP Publishing, 2019)
Braking is the necessary system need to install as the safety feature for moving transportation. Using the mechanical braking only as primary braking system in Electric Transportation (ET) is insufficient due to some issues such as low strength users hand gripping and abruptly tire locking during braking especially on wet surface condition. In this paper, the performance between mechanical and electrical braking which is by using dynamic braking concept is proposed to enhance the braking performance of Electric Powered Wheelchair (EPW). The experiments were conducted during descending on the slope under wet and dry pavements. From the results of slip ratio, the slipping time between mechanical and dynamic braking in dry pavement is recorded 0.9 seconds and 0.7 seconds respectively. Meanwhile, it is observed that tire is fully locked-up for mechanical braking under the wet surface. However, by using the dynamic braking, the wheel does not lock-up and the slipping time was recorded 1.4 seconds. It can be considered that, mechanical and dynamic braking give their own merit. The high braking torque from mechanical braking is suitable to use under the dry pavement for the short stopping distance. The other sides, braking under the wet pavement, dynamic braking is more efficient compare to the mechanical braking in term of short slipping time and does not cause tire to lockup while braking.